Combined Predictive Value of Neutrophil-to-Lymphocyte Ratio and CHA2DS2-VASc Score for Cardiogenic Cerebral Embolism in NVAF Patients - Hu J; Wang JJ; Wang L; Cao YH; Wu JC (International Journal of General Medicine, 2025)
Jie Hu,1,2,* Jing-Jing Wang,2,3,* Long Wang,1,2 Yong-Hong Cao,2,3 Jun-Cang Wu1,2 1Department of Neurology, Hefei Hospital Affiliated to Anhui Medical University (The Second People’s Hospital of Hefei), Hefei, Anhui, 230011, People’s Republic of China; 2The Fifth Clinical Medical College of Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of China; 3Department of Endocrinology, Hefei Hospital Affiliated to Anhui Medical University (The Second People’s Hospital of Hefei), Hefei, Anhui, 230011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong-Hong Cao, Department of Endocrinology, Hefei Hospital Affiliated to Anhui Medical University (The Second People’s Hospital of Hefei), Hefei, Anhui, 230011, People’s Republic of China, Email fish1982cao@126.com Jun-Cang Wu, Department of Neurology, Hefei Hospital Affiliated to Anhui Medical University (The Second People’s Hospital of Hefei), Hefei, Anhui, 230011, People’s Republic of China, Email wujuncang126@126.comAim: This study aimed to determine the identification role of neutrophil-to-lymphocyte ratio (NLR) combined with CHA2DS2-VASC score for cardiogenic cerebral embolism (CCE) in acute ischemic stroke patients with non-valvular atrial fibrillation (NVAF).Methods: From January 2019 to August 2024, a total of 402 acute ischemic stroke patients with NVAF were enrolled in this retrospective study and were divided according to the occurrence of CCE into the CCE or non-CCE groups. Clinical data were collected from both groups, which included demographic data, medical history, CHA2DS2-VASC score, and laboratory tests (blood cell counts and blood biochemistry indicators). A predictive model based on blood indexes and the CHA2DS2-VASC score was constructed using least absolute shrinkage and selection operator (LASSO) regression analysis.Results: Multiple regression analysis showed that the CHA2DS2-VASc score (OR = 2.95, 95% CI = 2.19– 3.99, p < 0.001), white blood count (OR = 1.43, 95% CI = 1.15– 1.78, p = 0.001), neutrophil-to-lymphocyte ratio (NLR; OR = 1.63, 95% CI = 1.29– 2.05, p < 0.001), and D-dimer levels (OR = 1.56, 95% CI = 1.15– 2.12, p = 0.005) were independent risk factors for CCE. Spearman correlation analysis showed that NLR and the CHA2DS2-VASc score had a significant positive correlation (R = 0.449, p < 0.001). The area under the receiver operating characteristic (ROC) curve (AUC) for NLR and the CHA2DS2-VASc score were 0.869 (95% CI = 0.843– 0.901) and 0.859 (95% CI = 0.820– 0.898), respectively. A composite index for distinguishing CCE risk was constructed using LASSO regression analysis, which yielded an AUC value of 0.924 (95% CI = 0.898– 0.950).Conclusion: NLR is an independent risk factor for CCE in NVAF patients, and combining it with CHA2DS2-VASC score provides a more useful composite index for identifying the CCE risk of patients with NVAF. This composite score may serve as a promised tool in clinical workflows, and it could even contribute to individualized anticoagulation strategies by identifying high-risk patients who may benefit from more positive preventive methods.Keywords: non-valvular atrial fibrillation, cardiogenic cerebral embolism, CHA2DS2-VASc score, neutrophil-to-lymphocyte ratio, neutrophil extracellular traps, least absolute shrinkage and selection operator